Methodological Remarks on Anti-equilibrium by Janos Kornai - Musialik, Rafał (Metodologiczne uwagi na temat Anti-equilibrium Janosa Kornaia, 2023)
The subject of this paper is Kornai’s concept as contained in Anti-equilibrium. The aim of the paper was to provide a critical analysis of this concept. The analysis focused on the methodological aspect of Anti-equilibrium, namely on the concept of the explanation adopted by the Hungarian economist. The research method used is textual analysis. The result of this analysis allows, as it seems, to see an important methodological flaw of Anti-equilibrium. The thesis of this article is that this defect did not allow Kornai’s proposal to be treated as a viable competitor to neoclassical economics.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 4, s. 114-120
Keywords: general equilibrium theory; neoclassical economics; methodology of economics; centrally planned economies; teoria równowagi ogólnej; ekonomia neoklasyczna; metodologia ekonomii; gospodarki centralnie planowane